Association between carotid intima‐media thickness and fasting blood glucose level: A population‐based cross‐sectional study among low‐income adults in rural China. Issue 6 (22nd March 2017) - Gao, Liu; Bai, Lingling; Shi, Min; Ni, Jingxian; Lu, Hongyan; Wu, Yanan; Tu, Jun; Ning, Xianjia; Wang, Jinghua; Li, Yukun
Abstract : Age and hypertension were public determinants of increased CIMT in normal FBG, IFG and DM group. Moreover, male sex, smoking, and high LDL‐C level were positively associated with increased CIMT in normal FBG group; high TG level was negatively associated with the mean CIMT in the IFG group; and alcohol consumption was an independent risk factor for mean CIMT in the DM group. Hypertension was the greatest risk factor for increased CIMT. Abstract: Aims/Introduction: Carotid intima‐media thickness (CIMT) is an established predictor of cardiovascular disease and stroke. We aimed to identify the association between CIMT and blood glucose, as well as the risk factors associated with increased CIMT in a low‐income Chinese population. Materials and Methods: Stroke‐free and cardiovascular disease‐free residents aged ≥45 years were recruited. B‐mode ultrasonography was carried out to measure CIMT. Results: There were 2, 643 participants (71.0%) in the normal group, 549 (14.7%) in the impaired fasting glucose group and 533 (14.3%) in the diabetes mellitus group. The determinants of increased CIMT were older age; male sex; low education; hypertension; smoking; high levels of systolic blood pressure, fasting blood glucose and low‐density lipoprotein cholesterol; and low levels of diastolic blood pressure, triglycerides and high‐density lipoprotein cholesterol, after adjusting for covariates. Age and hypertension were the common risk factors for increased CIMT in all three groups. Furthermore, male sex, smoking and high low‐density lipoprotein cholesterol level were positively associated with the mean CIMT in the normal group; high triglycerides levels were negatively associated with the mean CIMT in the impaired fasting glucose group; and alcohol consumption was an independent risk factor for mean CIMT in the diabetes mellitus group. Hypertension was the greatest risk factor for increased CIMT. Conclusions: These findings suggest that it is crucial to manage and control traditional risk factors in low‐income populations in China in order to decelerate the recent dramatic increase in stroke incidence, and to reduce the burden of stroke.